Biomedical applications of nano technologies : proceedings of the International Symposium "Biomedical Applications of Nano Technologies" of the Forum on New Materials, part of CIMTEC 2006-11th International Ceramics Congress and 4th Forum on New Materials, held in Acireale, Sicily, Italy on June 4-9, 2006 - Vincenzini, P.; Barbucci, R. (Advances in science and technology (Faenza, Italy) ;, 2006)
This collection presents 18 papers. Altogether, the collection a wealth of offers up-to-date information on Biomedical Applications of Nano Technologies. CIMTEC 2008: http://www.cimtec-congress.org.